Negotiation skills training - Downs, Lisa J. (ASTD trainer's workshop series, 2008)
"Anyone can learn how to negotiate with proper training. Negotiation Skills Training offers a unique five-step process and practical exercises to help learners present clear and convincing arguments to develop and improve the vital skill of negotiation. Part of the ASTD Trainer's Workshop series--ASTD's done all the work for you with complete, customizable, ready-to-use programs. Titles offer half-day, one-day, and two-day workshop formats, as well as all the exercises, handouts, assessments, structured experiences, and presentations needed for effective delivery. PowerPoint slides and electronic copies of all supporting materials for this title are provided online as downloadable content."--Publisher's description